Influence de l'âge de la feuille sur les paramètres biologiques et les populations de l'acarien vert du manioc Mononychellus tanajoa Bondar (Acari: tetranychidae) - Badegana, AM.; Yombo, G. (Tropicultura, 2002)
The Effect of Leaf Age on the Cassava Green Mite Mononychellus tanajoa Bondar (Acari: Tetranychidae) Biological Parameters and Population Growth Rates. The study of cassava (Manihot esculenta Crantz) leaf age effect on Mononychellus tanajoa Bondar biological parameters and population growth rates was studied in laboratory (T= 24-26 °C; RH= 70-90%). The local Dschang cultivar was used and the study concerned the 15, 40, 65, 90 and 115 days old leaves. The results obtained show that the egg incubation duration was the longest (6.4 days) and that of the deutonymph stage the shortest one (1.9 days). The hatching rate was very high (98%). There was no significant difference (p= 0.05) between the developmental stages of M. tanajoa reared on the leaves of different ages. On the contrary fecundity whatever it is daily or total was high on young leaves and small on the old ones. The correlation coefficient between the leaf age and the intrinsic rate of increase (rm) was -0.896 and that obtained between the net reproduction rate (Ro) and the leaf age -0.966. These coefficients are negative and in absolute value near to one; which shows that the more the leaf is old, the more the M. tanajoa population growth is little. The M. tanajoa population growth is therefore fast on young leaves and slow on the old ones.